Characterization of the Ashbya gossypii secreted N-glycome and genomic insights into its N-glycosylation pathway - Aguiar, Tatiana Quinta (2013)
The riboflavin producer Ashbya gossypii is a filamentous hemiascomycete, closely related to the yeast Saccharomyces cerevisiae, that has been used as a model organism to study fungal developmental biology. It has also been explored as a host for the expression of recombinant proteins. However, although N-glycosylation plays important roles in protein secretion, morphogenesis, and the development of multicellular organisms, the N-glycan structures synthesised by A. gossypii had not been elucidated. In this study, we report the first characterization of A. gossypii N-glycans and provide valuable insights into their biosynthetic pathway. By combined matrix-assisted laser desorption-ionization time-of-flight (MALDI-TOF) mass spectrometry profiling and nuclear magnetic resonance (NMR) spectroscopy we determined that the A. gossypii secreted N-glycome is characterized by high-mannose type structures in the range Man4–18GlcNAc2, mostly containing neutral core-type N-glycans with 8–10 mannoses. Cultivation in defined minimal media induced the production of acidic mannosylphosphorylated N-glycans, generally more elongated than the neutral N-glycans. Truncated neutral N-glycan structures similar to those found in other filamentous fungi (Man4–7GlcNAc2) were detected, suggesting the possible existence of trimming activity in A. gossypii. Homologs for all of the S. cerevisiae genes known to be involved in the endoplasmatic reticulum and Golgi N-glycan processing were found in the A. gossypii genome. However, processing of N-glycans by A. gossypii differs considerably from that by S. cerevisiae, allowing much shorter N-glycans. Genes for two putative N-glycan processing enzymes were identified, that did not have homologs in S. cerevisiae.